A Optimization Of Digital Zakat In The Perspective Of Sharia Economic Law And Good Governance (Field Study On Baznas Ponorogo Regency) - Wijahudin, Anas; Aprilia, Dwi; Widari, Ratnasari (Journal of Sharia Economic Law, 2025)
Digitization of zakat management is one of the key strategies to increase the effectiveness of zakat collection and distribution in Indonesia. The National Amil Zakat Agency (BAZNAS) of Ponorogo Regency, as the official zakat management institution, has implemented a digital zakat system to expand the reach of muzakki and increase the transparency of zakat fund management. This study aims to analyze the optimization of digital zakat in BAZNAS Ponorogo Regency from the perspective of sharia economic law and the principle of good governance. This study uses a field research method with a descriptive qualitative approach. Data were obtained through in-depth interviews with BAZNAS Ponorogo Regency management, observation, and documentation. The results of the study show that the implementation of digital zakat at BAZNAS Ponorogo Regency is in accordance with the principles of sharia economic law, particularly trust, transparency, justice, and benefit. In addition, the application of good governance principles is reflected in greater accountability reporting, increased information disclosure, and greater community participation. Nevertheless, the optimization of digital zakat still faces challenges, including limited digital literacy among the community and insufficient technical regulations. Therefore, it is necessary to strengthen digital zakat governance and education to achieve professional, sustainable zakat management.